2011
DOI: 10.1017/s0033291711002406
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in patients with first-episode schizophrenia: a longitudinal perspective

Abstract: Background. This study aimed to identify the course of unmet needs by patients with a first episode of schizophrenia and to determine associated variables.Method. We investigated baseline assessments in the European First Episode Schizophrenia Trial (EUFEST) and also follow-up interviews at 6 and 12 months. Latent class growth analysis was used to identify patient groups based on individual differences in the development of unmet needs. Multinomial logistic regression determined the predictors of group members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 51 publications
3
38
0
3
Order By: Relevance
“…In the only longitudinal study published so far on the needs of first-episode schizophrenia patients, results showed that daily activities, psychotic symptoms, psychological stress, and social integration were most frequently reported as unmet needs. In the follow-up, second-generation medication showed no effect on the course of unmet needs 92. Antipsychotic treatment alone was not sufficient to account for the psychosocial needs of patients.…”
Section: Unmet Psychosocial and Economic Needsmentioning
confidence: 87%
“…In the only longitudinal study published so far on the needs of first-episode schizophrenia patients, results showed that daily activities, psychotic symptoms, psychological stress, and social integration were most frequently reported as unmet needs. In the follow-up, second-generation medication showed no effect on the course of unmet needs 92. Antipsychotic treatment alone was not sufficient to account for the psychosocial needs of patients.…”
Section: Unmet Psychosocial and Economic Needsmentioning
confidence: 87%
“…These familial differences between the genders could be attributed to cultural gender role expectations, higher levels of conflict and fear in families of men due to their higher aggression rates (Leung & Chue, 2000), and greater attribution of self-blame and guilt in parents of early onset males (Seeman, 2004). With the onset of psychotic illness, further social deterioration is common, particularly in the first few years (an der Heiden & Häfner, 2000): the EUFEST study has identified daytime activities and social integration as amongst the greatest unmet needs in psychosis (Landolt et al, 2012).…”
Section: Social Differencesmentioning
confidence: 99%
“…; Landolt et al . ; Schlithler et al . ), with one additional article meeting criteria for Part B, but not Part A (Landolt et al .…”
Section: Resultsmentioning
confidence: 99%
“…The term ‘need’ has been defined in healthcare contexts as a ‘prerequisite for maintaining or restoring an acceptable level of social independence and quality of life’ (Landolt et al . , p;.1462; McCrone et al . ).…”
Section: Introductionmentioning
confidence: 98%